The Use Of Spotify Appication To Teach Listening Skill - Eka Agustina; Hastuti Retno Kuspiyah; Ade Triani (Jurnal Pendidikan dan Sastra Inggris, 2023)
This research was conducted to find out whether any significant difference between students who are taught by using Spotify Application and the students who are taught by using coventional media toward their listening skill at the eighth grade students of SMP Pangudi Luhur Sukaraja. The type of the research used quantitative research, with experimental method and quasi experimental design. The population was the Eighth grade students of SMP Pangudi Luhur Sukaraja in academic year 2023/2024. The sample was taken by using Purposive Sampling, consisted of experimental group with 21 students and control group with 20 students. The research was collected using completion test and analyzed with the independent t-test SPSS 22. The result of tobtained was higher than ttable (4.213 > 2.022) and the value of sig. (2 tailed)=0.000 less than the value of significance level (0.05). So, the null hypothesis (Ho) was rejected and the alternative hypothesis was accepted. The finding of the research showed that there is a sigificant difference between experimental group and control group. This meant that Spotify Application is suitable to used in teaching and learning listening  skill at the eighth grade students of SMP Pangudi Luhur Sukaraja.